The effectiveness of potassium phosphite and captan mixture in controlling Venturia inaequalis in apple orchards (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2014)
Venturia inaequalis is a common apple disease in Serbia and its intensity depends on weather conditions. The most successful method of combating apple scab is to use a lower dose of an active ingredient and increase its effectiveness by adding substances that do not cause environmental damage. The effectiveness of a fungicide mixture of captan and potassium phosphite against V. inaequalis was investigated in apple orchards in 2008 and 2009. The relevant EPPO standard method was used in all trials. Captan 50 WP was used as a standard fungicide. In order to determine the exact conditions marking the onset of apple infection, key meteorological conditions were monitored in the orchards using an automated iMetos weather station and a Lufft electronic instrument. The results showed high efficacy of the tested fungicides which remained similar in both years of investigation. The intensity of leaf infection after treatment with the mixture of captan and potassium phosphite was 0.7-2.4%, while fruit infection was 0.5-3.0%. The efficacy of this mixture ranged from 96.3-97.9% on leaves and 87.4-98.7% on fruits. The standard fungicide Captan 50 WP showed an efficacy ranging from 95.3-96.7% on leaves and from 87.8-99.3% on fruits. No statistically significant differences were found between the fungicide tested and the standard fungicide.
Keywords: Apple scab; Potassium-phosphite; Captan; Effectiveness